USE OF INFLIXIMAB IN THE CASE OF INFLAMMATORY BOWEL DISEASE IN CHILDREN - N.E. Shchigoleva; I.A. Matina; A.P. Ponomareva; L.M. Karpina; A.A. Bologov (Union of pediatricians of Russia, 2010)
The Article is focused on the pressing issue, i.e. the therapy of inflammatory bowel diseases. It reviews in detail the aspects of using monoclonal antibodies to the tumor necrosis factor in the case of Crohn's disease and unspecific ulcerative colitis. The article describes the results of the authors' observations and provides data obtained by foreign researchers.Key words: ulcerative colitis, Crohn's disease, treatment, Infliximab, antibodies to the tumor necrosis factor, children. (Pediatric Pharmacology. - 2010; 7(1):55-61)